DIGITAL ELECTRONIC PRACTICUM WITH LOGISIM APPLICATION USING WHATSAPP VIDEO CALL - Dewi Dewantara (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study was to describe the effectiveness and response of students about the Digital Electronics Practicum with the Logisim Application Using Whatsapp Video Call. This type of research is descriptive research. The research subjects were 50 Physics Education Students of Lambung Mangkurat University taking Digital Electronics courses. Data collection techniques are through practicum assessment sheets and student response questionnaires. The results of the student response questionnaire showed that the format, quality, clarity, and interest of the students were in good categories. The results of student practicum assessments show the effectiveness of the Digital Electronics Practicum with the Logisim Application Using Whatsapp Video Call in the good category. Thus it can be concluded that the Digital Electronics Practicum with Logisim Applications Using Whatsapp Video Call is effective to be implemented and gets a very good response from students..